Path Analysis of Critical Thinking Effect on Self-Efficiency Among Nursing and Medical Students - Omid Khosravizadeh; Bahman Ahadinezhad; Aisa Maleki; Ailar Hashtroodi; Pariya Vosoughi; Shahrzad Kohan (Shahid Sadoughi University of Medical Sciences, 2022)
Background: Critical thinking is the ability to ask appropriate questions and gather relevant information. It enables rational judgment and problem-solving for physicians and nurses. For the first time, this study examined two major groups of caregivers at the patient's bedside in terms of the relationship between critical thinking and self-efficacy. Methods: This was a descriptive-analytical and cross-sectional study conducted in 2021. The sample was taken from QUMS's nursing and medical students through stratified random method. It was performed using structural equation method (n=377). Data collection tools included: demographic information, Ricketts critical thinking questionnaire, and GSE-17 questionnaire. Finally, data were analyzed through the correlation coefficient and multiple regression tests using SPSS22 software at a significance level of 0.05. Results: Results indicated that the model established at this step demonstrates good fitness. In this model χ2 = 1919.91, df = 89, χ2 / df = 2.14, RMSEA = 0.05, NFI = 0.63, GFI = 0. 77 and CFI = 0. 76.   The structural equation model's standard estimation coefficients show that all the existing paths are at a significant level (CTH: CRV 0.96, CTH: COM 0.94, CTH: SFE -0.61; P-value< 0.05). Finally, the regression analysis showed an inverse effect of critical thinking on self - efficacy. Conclusion: The study showed that critical thinking had a direct effect on self-efficacy. In addition, these two features have a significant effect on increasing the efficiency and making the right clinical decisions in medical and nursing groups. Therefore, upgrading these skills by updating curriculum will ultimately improve healthcare outcomes provided by these two specific groups.